Prioritization of service quality dimensions for healthcare sector using analytic hierarchy process - Islam, Rafikul (2017)
Due to the unique nature among the service industries, the overriding objective of the healthcare sector is to provide error free, impeccable services to their patients and clientele. It is not an option rather a norm for the healthcare sector to uphold and maintain the level of service that is quintessential and benchmark in the service industries. However, service quality has different meanings to different people. In this paper, SERVQUAL has been considered as the main tool to measure service quality and Analytic Hierarchy Process (AHP) has been applied to prioritize the five dimensions of SERVQUAL for healthcare sector. In addition to this, AHP has been applied to prioritize the various items representing each of the dimensions. The results show that Reliability and Assurance are the two most important service quality dimensions in the healthcare sector. The priorities of dimensions and their items are also determined with respect to a selected demographic factors on the part of the respondents.